Stratigraphy and Foraminiferal Biostratigraphy of Sentolo Formation in Sedayu Area: Local Unconformity Identification in Early Pliocene - Akmaluddin Akmaluddin; Muhammad Virgiawan Agustin; Ma’ruf Kurniawan Adi (Geological Engineering Department Universitas Gadjah Mada, 2019)
The study area is located in Sedayu District, Bantul Regency, Special Region of Yogyakarta Province which belongs to the Sentolo Formation. This area is an interesting place to study because there are erosional boundaries that indicate an unconformity in the Sentolo Formation. In this study, stratigraphic measurements and sampling were carried out in the field, then the samples were prepared and analyzed for the content of planktic and benthic foraminifera fossil. The results of the analysis are the determination of biozonation, paleobathimetry, and identification of sedimentation rates and unconformity. From the data analysis, ware known that the Sentolo Formation in Sedayu area can be divided into three lithofacies, namely thickening upward calcareous sandstone – calcareous siltstone facies, channel calcareous sandstone – calcareous siltstone facies andthinning upward limestone facies. Based on the biostratigraphy analysis, can be divided into four biozonations, namely the PL1A, PL1B, PL1C, and PL2 zones which are included in the Early Pliocene age. There is an unconformity in the facies boundary of the channel calcareous sandstone – calcareous siltstone facies with thinning upward limestone facies, identified by the presence of an erosional boundary at that interval and also supported by sudden changes in paleobatimetry from Upper Bathyal to Middle Neritic. The sedimentation rate identified in this area has a value of 15.5 m / Ma which identified in the lower facies. The extrapolation results of age and sedimentation rates concluded that the unconformity occurred at 4.46–4.20 Ma, and eroded 4.03 m thick of sedimentary rocks